2016
DOI: 10.1063/1.4958295
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metal layer thickness on spin-orbit torque and current-induced switching in Hf|CoFeB|MgO structures

Abstract: We study the heavy metal layer thickness dependence of the current-induced spin-orbit torque (SOT) in perpendicularly magnetized Hf|CoFeB|MgO multilayer structures. The damping-like (DL) current-induced SOT is determined by vector anomalous Hall effect measurements. A non-monotonic behavior in the DL-SOT is found as a function of the thickness of the heavy-metal layer. The sign of the DL-SOT changes with increasing the thickness of the Hf layer in the trilayer structure. As a result, in the current-driven magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 27 publications
4
18
0
1
Order By: Relevance
“…et al, 2013b), so that separating the bulk and interface contributions to ξ j DL is not straightforward. Moreover, a change of sign of both ξ j DL and ξ j FL has been reported for Ta/CoFeB/MgO (Allen et al, 2015;Kim et al, 2013a) and Hf/CoFeB/MgO (Akyol et al, 2016;Ramaswamy et al, 2016) at t Ta ≈ 0.5 nm and t Hf ≈ 2 nm, respectively, indicating that there are different mechanisms contributing to the torques that may compete or reinforce each other.…”
Section: Metal Alloysmentioning
confidence: 90%
See 1 more Smart Citation
“…et al, 2013b), so that separating the bulk and interface contributions to ξ j DL is not straightforward. Moreover, a change of sign of both ξ j DL and ξ j FL has been reported for Ta/CoFeB/MgO (Allen et al, 2015;Kim et al, 2013a) and Hf/CoFeB/MgO (Akyol et al, 2016;Ramaswamy et al, 2016) at t Ta ≈ 0.5 nm and t Hf ≈ 2 nm, respectively, indicating that there are different mechanisms contributing to the torques that may compete or reinforce each other.…”
Section: Metal Alloysmentioning
confidence: 90%
“…Such a phenomenological parameter, however, accounts for the transmission of the bulk spin current as much as for the generation of interface spin currents, so that its use to estimate an asymptotic value of the bulk SHE in NMs can be questioned. Moreover, the spacer layer itself can be regarded as a source of spin current, as has been shown in the case of Hf (Akyol et al, 2016;Ramaswamy et al, 2016).…”
Section: Metal Alloysmentioning
confidence: 98%
“…To increase the efficiency of magnetization switching by SOTs, it is crucial to search for materials with large spin Hall angle (the ratio between spin current density and charge current density). Metals with strong spin–orbit coupling such as Pt, Ta, Pd, W, Hf, etc., have been widely studied in the past several years. It has been reported that the spin Hall angle is significantly related to the crystalline structure and can be varied by changing the thickness or by oxidation …”
Section: Manipulation Of Magnetic Materials By Spin–orbit Torquesmentioning
confidence: 99%
“…SOTs with both a fieldlike and dampinglike character can manifest in such systems, with the latter capable of driving magnetization switching [1][2][3][4][5]7,9,[11][12][13]15,21,22,24] and magnetic domain wall motion [26][27][28][29][30][31]. SOTs have been identified and quantified by a variety of techniques including spin-torque ferromagnetic resonance [2,7,14,17,19,25], quasistatic magnetization tilting probed through harmonic voltage measurements [6,[8][9][10][11][12][13]17,[19][20][21][22][23][24][25][26]28,31], and current-induced hysteresis loop shift measurements [18,32,33]. Most studies of SOTs have focused on ultrathin metallic ferromagnet/heavy-metal bilayers with interfacial perpendicular magnetic ani...…”
mentioning
confidence: 99%
“…SOTs have been identified and quantified by a variety of techniques including spin-torque ferromagnetic resonance [2,7,14,17,19,25], quasistatic magnetization tilting probed through harmonic voltage measurements [6,[8][9][10][11][12][13]17,[19][20][21][22][23][24][25][26]28,31], and current-induced hysteresis loop shift measurements [18,32,33]. Most studies of SOTs have focused on ultrathin metallic ferromagnet/heavy-metal bilayers with interfacial perpendicular magnetic anisotropy (PMA) [1][2][3][5][6][7][8][9][11][12][13][15][16][17][18][19][20][21][22][23][24][25]…”
mentioning
confidence: 99%